Effectiveness of Pentoxifylline Therapy for Management of Oral Submucous Fibrosis - Bajgai, Dwarika Prasad; Agrawal, Bela; Yadav, Abadhesh (Journal of Nepalgunj Medical College, 2022)
Introduction: Oral submucous fibrosis is a chronic oral disease characterized by progressive buildup of constricting collagen bands in the cheeks and adjacent structures of the mouth due to chewing of areca nut. This can severely restrict mouth opening and tongue movement causing pain and burning sensation in the mouth.Aims: This study evaluates the efficacy of pentoxifylline in the management of oral submucous fibrosis.Methods: A hospital-based study, conducted in the dental outpatient department of Nepalgunj Medical College from October 2019 to September 2020. Forty-nine patients who were diagnosed histopathologically with oral submucous fibrosis were included. The patients were divided into two groups. In group A, patients were given, 200 mg thrice daily for first 30 days, then dose hiked to 400 mg thrice daily for two more months. Group B patients received treatment with multi-vitamin capsules (B-complex one capsule before sleep daily) for three months. All patients were followed up for six months and were assessed for maximum inter-incisor opening, pain on opening of mouth and burning sensation.Results: There was no statistical difference in mouth opening at baseline and first follow up. The mouth opening was significantly more in group A compared to group B from second follow up which persisted till third follow up (p